Experimental Study on Load Bearing Characteristics of Steel Fiber Reinforced Concrete Lining in the Soft Surrounding Rock Tunnel - Guang-yao Cui; Jia-suo Qi; Dao-yuan Wang (Advances in Civil Engineering)
Tunnels in soft rock with high ground stress will encounter the problem of large deformation of surrounding rock. The study of new high-performance tunnel lining materials is of great significance to improve the safety of tunnel excavation in soft rock with high ground stress. In this paper, the bearing characteristics of the plain concrete, the reinforced concrete, and the steel fiber reinforced concrete lining are studied by the indoor model experiment. By extracting the displacement and stress data of typical parts of lining, the bearing characteristics of the steel fiber reinforced concrete lining are analyzed and summarized. The test results show that the initial crack load and ultimate load of the steel fiber reinforced concrete lining are significantly higher than those of the other two materials, and the crack development path is more tortuous, and the number of cracks is greater. Steel fiber can improve the bearing capacity and deformation capacity of the lining structure so that the failure mode of the lining structure changes from brittle shear failure to ductile bending failure. It is concluded that steel fiber reinforced concrete can improve the toughness of lining. Because of its excellent mechanical properties, steel fiber reinforced concrete can completely replace the conventional reinforced concrete as a new lining material for soft rock tunnel. The above research results are of great significance to the design and construction of tunnel lining in the soft surrounding rock.